Sphagnum capillifolium holobiont from a subarctic palsa bog aggravates the potential of nitrous oxide emissions - Nie, Yanxia; Lau, Sharon Yu Ling; Tan, Xiangping; Lu, Xiankai; Liu, Suping; Tahvanainen, Teemu; Isoda, Reika; Ye, Qing; Hashidoko, Yasuyuki (Frontiers in Plant Science, 2022)
Melting permafrost mounds in subarctic palsa mires are thawing under climate warming and have become a substantial source of hot spots for N2O emissions. However, mechanistic insights into the permafrost thaw-induced N2O emissions in these unique habitats remain elusive. We demonstrated that N2O emission potential in palsa bogs was driven by the bacterial residents of two dominant Sphagnum mosses in the subarctic palsa bog, which responded to endogenous and exogenous Sphagnum factors such as secondary metabolites, nitrogen and carbon sources, temperature, and pH. Sphagnum capillifolium (SC)'s high N2O emission activity was linked with two classes of distinctive hyperactive N2O emitters, including Pseudomonas sp. and Enterobacteriaceae bacteria, whose hyperactive N2O emitting capability was characterized to be dominantly pH-responsive. As the nosZ gene-harboring emitter, Pseudomonas sp. SC-H2 reached a high level of N2O emissions that increased significantly with increasing pH. For emitters lacking the nosZ gene, an Enterobacteriaceae bacterium SC-L1 was more adaptive to natural acidic conditions, and N2O emissions also increased with pH. Our study revealed previously unknown hyperactive N2O emitters in Sphagnum capillifolium found in melting palsa mound environments, and provided novel insights into SC-associated N2O emissions.